Greenhouse Gas Emissions as a Strategic Financial Variable: A Systematic Literature Review and Bibliometric Analysis of the Manufacturing Industry - Agus Rianto; Udisubakti Ciptomulyono (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
Climate change has intensified regulatory pressure and market expectations for corporate decarbonization, particularly in carbon-intensive sectors such as manufacturing. Although numerous empirical studies have examined the relationship between greenhouse gas (GHG) emissions and financial performance, findings remain fragmented and sometimes divergent, creating uncertainty regarding the conditions under which emissions influence firm outcomes. This study synthesizes empirical evidence on the relationship between GHG emissions and financial performance in manufacturing firms through a systematic literature review of 16 studies published between 2019-2025, complemented by bibliometric analysis using VOSviewer to identify thematic clusters, research density, and temporal evolution. The results reveal a shift from treating emissions as environmental externalities toward conceptualizing them as strategic variables embedded within firm-level economic systems. Positive financial outcomes are more frequently observed when emission reduction aligns with efficiency improvements and technological progress, whereas short-term accounting effects and market-based responses may diverge depending on regulatory design and institutional context. The evidence indicates that the financial implications of carbon-related mechanisms are conditional on governance quality, policy design, market maturity, and performance measurement. These findings provide an integrative, contingency-oriented understanding of how decarbonization interacts with firm performance across heterogeneous institutional settings.